Labour markets in terms of the fourth industrial revolution - Trenovski, Borce; Trpkova-nestorovska, Marija; Merdzan, Gunter; Kozheski, Kristijan (Faculty of Economic-Prilep, University St. Kliment Ohridski”-Bitola, 2019)
Recently, many studies and analysis confirmed that the world is at the beginning of a powerful process of transformation that will radically change our lives, ways of working and relationships. Recent assessments have shown that about 65% of children entering primary school today will ultimately end up working in completely new job types that don’t exist nowadays. No one can predict what the job market will look like in 2050. The Fourth Industrial Revolution is expected to improve the computerization of manufacturing industry and focuses on equipping of the production with high technology. Three main goals of Industry 4.0 could be highlighted: (1) Reducing the human factor in manufacturing and eliminating human errors. (2) Achievement a high level of manufacturing flexibility and creating conditions for designing products that meet the specific requirements of the consumer. (3) Intensification of the production process. According to an analysis by the World Economic Forum, Industry 4.0 is expected to cause a net loss of 5.1 million jobs over the next five yearsin 15 economies which account for approximately 65% of the world’s total workforce. Additional analyses of the demographic and socio-economic trends show that the labour market will experience radical changes in the future. This paper aims to present the main trends in this field, to explain the benefits of technology and digitalization for the global economy as well as to elaborate the importance of preparing different parts of society for consequences of the Fourth Industrial Revolution on the global labour market.
Keywords: fourth Industrial Revolution, robotization, labour market, future of jobs